Revisão do gênero Derobrachus Audinet-Serville, 1832 (Coleoptera, Cerambycidae, Prioninae) - Silva, Antonio Santos (Arquivos de Zoologia, 2007)
Derobrachus Audinet-Serville, 1832, a genus belonging to the Prioninae, and distributed between south United States and north of South America, is reviewed and divided in three groups without taxonomic status: Brevicollis species group, Sulcicornis species group and Apterus species group. Six new species are described: D. hovorei and D. thomasi from United States; D. chemsaki, from Mexico and Guatemala; D. wappesi, from Panama; D. drumonti and D. lingafelteri from Mexico. D. hovorei, a relatively common insect from United States, is a new name to D. geminatus sensu Lameere and others. Three species are reinstated: D. inaequalis (Bates, 1872), D. granulatus Bates, 1884 (both from D. sulcicornis LeConte, 1851), and D. smithi Bates, 1892 [ from D. longicornis (Bates, 1872)] . Three species are synonymized: D. megalophthalmus Tippmann, 1953 [ = D. inaequalis (Bates, 1872)] , D. forreri Bates, 1884 (= D. geminatus LeConte, 1853), and D. lepesmei Tippmann, 1953 (= D. megacles Bates, 1884). D. cylindroidus Bates, 1884 is transfered to Trichoderes Chevrolat, 1843 (Meroscelisini). Key in Portuguese and English to the species of Derobrachus is added.